Analisis Segmentasi Pasar Terhadap Keputusan Pembelian Pada CV Merapi Farma Herbal Di Kabupaten Sleman Daerah Istimewa Yogyakarta - Choirunnisa Sabilia; Wahyu Setya Ratri; Eska Stefani (JURNAL ILMIAH AGRITAS, 2023)
The research aims to analyze the influence of market segmentation on purchasing decisions at CV Merapi Farma Herbal in Sleman Regency, Special Region of Yogyakarta Special Region. This research uses descriptive research with a quantitative approach. The population in this research is consumers. The sampling technique used is non-probability sampling. Determining the number of samples used the lemeshow formula and the sample size was 100 respondents who had made purchases. Statistical tests use validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, R test, F test, and T test. The results of the study show that the variables geographic segmentation, demographic segmentation, psychographic segmentation, and behavioral segmentation have a significant effect simultaneously on purchasing decisions at CV Merapi Farma Herbal. The coefficient of determination value is 53% and the remainder is influenced by other variables not examined in this research. The geographic segmentation variable has a partially significant effect on purchasing decisions for CV Merapi Farma Herbal with a significance value of 0.003 < 0.05. The demographic segmentation variable has a partially significant effect on purchasing decisions for CV Merapi Farma Herbal with a significance value of 0.000 < 0.05. Psychographic segmentation variables have a partially significant effect on purchasing decisions for CV Merapi Farma Herbal with a significance value of 0.001 < 0.05. The behavioral segmentation variable has a partially significant effect on the purchasing decision of CV Merapi Farma Herbal with a significance value of 0.003 < 0.05. The segmentation variable that has a dominant significant influence is the demographic segmentation variable.